Orientación Emprendedora, Orientación al Aprendizaje, Orientación al Mercado y Performance: Empresas Familiares Versus Empresas No Familiares - Hernández-Linares, Remedios; López-Fernández, M. Concepción (European Journal of Family Business, 2020)
Firms develop and use multiple strategic orientations. However, the investigations considering more than one strategic orientation are scant and have paid scant attention to the singular context of family firms, despite the growing evidence of their special strategic behavior. To cover these research gaps, we analyze the combined effects of three strategic orientations (mainly, entrepreneurial orientation, learning orientation, and market orientation) on family firm’s performance, by comparing family firms and non-family firms from Spain and Portugal. Our results show that the entrepreneurial orientation is the strategic orientation with higher impact on family firm performance, followed by market orientation, so, our work offers family firms some insights to an improved performance. In addition our work contributes to literature by corroborating the idea of strategic equifinality.